Pengaruh Earning Per Share (EPS), Return On Equity (ROE) dan Net Profit Margin (NPM) terhadap Harga Saham (Studi Pada Perusahaan LQ-45 di Bursa Efek Indonesia periode 2016-2019) - Tri Anjaswati; Muhammad Agus Salim; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to examine and analyze the Effect of Earning Per Share (EPS), Return On Equity (ROE) and Net Profit Margin (NPM) on Stock Prices in LQ45 Companies on the IDX during the 2016-2019 period. The population that is the object of this research is all LQ45 companies listed on the IDX during the 2016-2019 period. The sampling technique used purposive sampling method, in order to obtain 31 companies. The data analysis method used in this research is normality test, classical assumption test and multiple linear analysis and research hypothesis testing. The results of the analysis show that partially Earning Per Share (EPS), has a negative and significant effect on stock prices, Return On Equity (ROE) has a positive and significant effect on stock prices and Net Profit Margin (NPM) has a positive and insignificant effect on stock price. Meanwhile, simultaneously EPS, ROE and NPM or all independent variables have a significant effect on stock prices. Keywords : Earning Per Share (EPS), Return On Equity ( ROE), and Net Profit Margin (NPM), Stock Price.